Implementasi dan Implikasi Undang-Undang Nomor 23 Tahun 2011 (Studi Pengelolaan Zakat Mal Pada Baznas Kabupaten Jember Tahun 2018) - Raudatus Sholiha; Sriyatin Sriyatin (Universitas Muhammadiyah Surabaya, 2019)
AbstractAct Number 23 of 2011 concerning the management of zakat is issued with the aim of optimizing the role of BAZNAS in the collection and distribution of zakat, infaq and shodaqoh (ZIS) in the community. However, the community has not fully understood the role of BAZNAS, including in Jember Regency. This study aims to examine the Implementation of Law Number 23 of 2011 concerning zakat maal management in Jember Regency along with its implications and problems by focusing on zakat mal management.This research is a descriptive qualitative research using primary data obtained through observations at the BAZNAS office of Jember Regency. The results of the study show that the management of zakat mall in BAZNAS Jember Regency is still not optimal. BAZNAS in Jember Regency was only established in 2017 so that the majority of people have not understood the importance of zakat management by zakat institutions.This also has implications for the management of zakat mal which is still not optimal. On the other hand, the fundamental problems that occur due to the low trust and understanding of the community towards zakat institutions that play a role in providing services to prospective muzakki to pay zakat mal and facilitate the collection and distribution process.Based on these problems, BAZNAS Jember Regency needs to conduct a massive socialization to the public regarding the role of BAZNAS and the importance of professional zakat management based on the applicable Act. In addition, there also needs to be support from the local government in order to be more optimized for the management of zakat malls in Jember Regency.Keywords: Zakat Mal, BAZNAS of Jember Regency, Act Number 23 Year 2011.